Technology Entrepreneurship Project [ENT 600] : Apple Inc / Muhammad Azwan Hamid - Hamid, Muhammad Azwan (2021)
This is an endeavor to grasp how the theories can be applied to a practical situation. As a student in UiTM Perlis, it is a part of a study for everyone to undergo a case study project. So, for this purpose, I got the chance to research a company entity that manufactures a product that deeply interests us, which is Apple Inc, technology company. First, the general information regarding the corporate has been collected. Information is gathered through the primary and secondary source. In the second part of the report contains the specialized subject studies. The objective of the project is to figure on the background, organizational structure, products, and services that Apple provides. In this case study, I have analyses the strength, weaknesses, opportunities, and threats of this company in the real business world by using SWOT analysis. Next, I studied regarding the product manufactured by Apple, which is primarily a standard technology utilized by the company for its selected product that we have chosen which is their iPhone smartphone. Here, I will be explaining the problems of the products that have grab my attention. The problem of the product that I discovered is the product are high price which makes difficulties for customer to have it for their daily live. Next, is the product has restrictions on the phone which is have lack of convenience for customer to used. And lastly, no variety of product and application developed by Apple has made it difficult for those who have a high expectation for the better iPhone mobile design and technology. In this study, I will be explaining deeper regarding the problems and I would also be discussing the alternatives solutions towards the problems.